2017
DOI: 10.1002/jbmr.2982
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Growth-Related Adaptations in Bone Microarchitecture, Geometry, Density, and Strength From Childhood to Early Adulthood: A Mixed Longitudinal HR-pQCT Study

Abstract: Sex differences in bone strength and fracture risk are well documented. However, we know little about bone strength accrual during growth and adaptations in bone microstructure, density, and geometry that accompany gains in bone strength. Thus, our objectives were to (1) describe growth related adaptations in bone microarchitecture, geometry, density, and strength at the distal tibia and radius in boys and girls; and (2) compare differences in adaptations in bone microarchitecture, geometry, density, and stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
68
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 51 publications
8
68
2
1
Order By: Relevance
“…Our finding of sex differences on trabecular microarchitecture in later puberty is consistent with previous work . The higher BV/TV in boys is due to thicker trabeculae, but little to no change in trabecular number .…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of sex differences on trabecular microarchitecture in later puberty is consistent with previous work . The higher BV/TV in boys is due to thicker trabeculae, but little to no change in trabecular number .…”
Section: Discussionsupporting
confidence: 92%
“…Corresponding small declines (1% to 2%) in Tb.Ar and increases (7% to 8%) in Tb.Th and Tb.Sp indicated consolidation/formation of cortex by fusion of (smaller) trabeculae because trabecular BV/TV and Tb.BMD remained unchanged. These findings add to the limited evidence characterizing bone strength and microarchitectural development during the accelerated phase of the pubertal growth spurt . Our observations appear comparable to prior prospective research indicating increases in bone strength, Ct.Th, and Tb.Th, and decrease in Tb.N in years preceding peak pubertal growth spurt (ie, APHV) .…”
Section: Discussionsupporting
confidence: 87%
“…Prospective HR‐pQCT evidence of bone strength and microarchitectural development in children and adolescents is scarce. Available evidence of bone strength development relies on mixed longitudinal cohort findings spanning from early adolescence to young adulthood . There is a need to complement this data with evidence from children and youth preceding or during the accelerated phase of the adolescent growth spurt because limb bone growth predominates during this period .…”
Section: Introductionmentioning
confidence: 99%
“…Our finding that MVPA positively predicted Tt.Ar at the distal tibia in early and mid‐puberty is consistent with previous studies in children and adolescents that demonstrated a positive relationship between PA (via accelerometry or self‐report) and CSA (by DXA and HSA) at the narrow neck, intertrochanter and proximal femur shaft, periosteal circumference at the tibial shaft (by pQCT), and Tt.Ar at the distal tibia (by HR pQCT) . Given that Tt.Ar at the distal tibia tends to plateau approximately 3 years after APHV, the period of accelerated growth during early and mid‐puberty represents the previously reported “window of opportunity” to enhance bone geometry through the osteogenic effect of PA …”
Section: Discussionmentioning
confidence: 84%
“…Our findings are consistent with a recent longitudinal study that used pQCT to assess bone and previous cross‐sectional studies that demonstrated a significant association between objectively measured PA (via accelerometer or pedometer) and pQCT‐ and HR‐pQCT‐ estimated bone strength. In our recent analysis of the HBSIII cohort, bone strength (F.Load by HR‐pQCT) increased by approximately 47% to 65% in boys and 59% to 91% in girls at the distal tibia and radius in the 4 years around peak growth . Considering the strong influence of maturation and other biological determinants of bone strength (ie, genetic factors account for approximately 83% of distal radius and 61% of tibial bone strength by pQCT), we view the significant relationship of MVPA with bone strength across growth in girls and boys as meaningful.…”
Section: Discussionmentioning
confidence: 93%